A Review of the Right to Freedom and Safety. Understanding the Reasonable Suspicion: Array - Pantea, Andrei (Acta Universitatis Danubius. Juridica, 2021)
The most common violations found by the Court were those associated with the violation of Article 5, paragraph 3, namely a lack of relevant and sufficient reasons for detention during the criminal proceedings. Another problem that arises in the cases against Moldova detention without reasonable suspicion. The existence of a reasonable suspicion that the person committed the crime stipulated in the criminal law is a „sine qua non” of her arrest and detention.